Staphylococcal entertotoxins of the enterotoxin gene cluster (egcSEs) induce nitric oxide- and cytokine dependent tumor cell apoptosis in a broad panel of human tumor cells - Terman, David; Serier, Asma; Dauwalder, Olivier; Badiou, Cedric; Dutour, A; Thomas, Damien; Brun, Virginie; Bienvenu, Jacques; Etienne, Jérôme; Vandenesch, François; Lina, Gerard (Frontiers in Cellular and Infection Microbiology, 2013)
The egcSEs comprise five genetically linked staphylococcal enterotoxins, SEG, SEI, SElM, SElN and SElO and two pseudotoxins which constitute an operon present in up to 80% of Staphylococcus aureus isolates. A preparation containing theses proteins was recently used to treat advanced lung cancer with pleural effusion. We investigated the hypothesis that egcSEs induce nitrous oxide (NO) and associated cytokine production and that these agents may be involved in tumoricidal effects against a broad panel of clinically relevant human tumor cells. Preliminary studies showed that egcSEs and SEA activated T cells (range: 11-25%) in a concentration dependent manner. Peripheral blood mononuclear cells (PBMCs) stimulated with equimolar quantities of egcSEs expressed NO synthase and generated robust levels of nitrite (range: 200-250 µM), a breakdown product of NO; this reaction was inhibited by NG-monomethyl-L-arginine (L-NMMA) (0.3 mM), an NO synthase antagonist. Cell free supernatants (CSFs) of all egcSE-stimulated PBMCs were also equally effective in inducing concentration dependent tumor cell apoptosis in a broad panel of human tumor cells. The latter effect was due in part to the generation of NO and TNF-α since it was significantly abolished by L-NMMA, anti-TNF-α antibodies respectively and a combination thereof. A hierarchy of tumor cell sensitivity to these CFSs was as follows: lung carcinoma>osteogenic sarcoma>melanoma>breast carcinoma>neuroblastoma. Notably, SEG induced robust activation of NO/TNFα-dependent tumor cell apoptosis comparable to the other egcSEs and SEA despite TNF-α and IFN-γ levels that were 2 and 8 fold lower respectively than the other egcSEs and SEA. Thus, egcSEs produced by S. aureus induce NO synthase and the increased NO formation together with TNF-α appear to contribute to egcSE-mediated apoptosis against a broad panel of human tumor cells.